Structural and magnetic properties of Mg‐doped nano‐α‐Fe2O3 particles synthesized by surfactant mediation–precipitation technique. Issue 1 (10th September 2012) - Mohapatra, M.; Layek, Samar; Anand, S.; Verma, H. C.; Mishra, B. K.
Abstract Nanosized hematite with 1.53% Mg well dispersed in the crystal could be prepared using a wet chemical method. The chemical reaction followed by aging at 60 °C for 12 h produced Mg‐doped hematite of mean crystallite size (MCD) 78 nm as shown by X‐ray diffraction. Transmission electron microscopy measurement showed that particles are nearly spherical in shape. However, FTIR and differential thermal analysis results indicated presence of ferric hydroxide phase which was also confirmed from Mössbauer spectroscopy. The sample annealed at 400 °C did not show any extra phase other than α‐Fe2O3. Mg‐doped α‐Fe2O3 showed a weak ferromagnetism with a hysteresis loop superimposed on antiferromagnetic M–H curve. The saturation magnetization and coercivity decreased when the sample was annealed at 400 °C. The presence of ferrihydrite in α‐Fe2O3 matrix seems to provide pinning centers for domain walls, increasing the coercivity showing that this composite can also be an interesting magnetic material. Mössbauer spectrum of (a) as‐prepared and (b) annealed sample of Mg‐doped hematite recorded in transmission geometry at 300 K. Black circles are the experimental data points and solid blue line is the Lorentzian fit. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>